The Trade Effects of U.S. Antidumping Actions - Thomas J. Prusa (Rutgers University, Department of Economics, 1996)
In this paper I present evidence on the effectiveness of AD actions. Using a data set based on the line-item tariff codes identified in the cases, I examine the trade patterns of both countries named in the petition and those countries not subject to the investigation. Several important finding emerge. First, AD duties substantially restrict the volume of trade from named countries, especially for those cases with high duties. Second, AD actions that are rejected still have an important impact on named country trade, especially during the period of investigation. Third, there is substantial trade diversion from named to non-named countries and the diversion is greater the larger is the estimated duty. Because of the diversion of imports, the overall volume of trade continues to grow—even for those cases which result in duties. Fourth, despite the diversion of imports, AD law still offers important benefits because it induces substantial import prices increases both by named and non-named countries. Finally, because of the diversion of imports, aggressive use of AD law by U.S. firms has the peculiar side-effect of benefiting non-named countries who are active in the areas under investigation.
Keywords: O34; 330; AD actions; import diversion; trade restrictions